2021
DOI: 10.3389/fgene.2021.674539
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Shellome’ of the Crocus Clam Tridacna crocea Emphasizes Essential Components of Mollusk Shell Biomineralization

Abstract: Molluscan shells are among the most fascinating research objects because of their diverse morphologies and textures. The formation of these delicate biomineralized structures is a matrix-mediated process. A question that arises is what are the essential components required to build these exoskeletons. In order to understand the molecular mechanisms of molluscan shell formation, it is crucial to identify organic macromolecules in different shells from diverse taxa. In the case of bivalves, however, taxon sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Several protease inhibitors belonging to five distinct families, i.e., kazal-type, kunitztype, tissue inhibitor of metalloprotease (TIMP), whey acidic protein (WAP), and alpha-2macroglobulins (A2M), were upregulated at T1. As previously noted by other authors [79], protease inhibitors are a recurrent theme in shell biomineralization proteomes, where they are believed to prevent the premature degradation of extracellular matrix proteins by the numerous proteolytic enzymes present in the extracellular space. Among these five protease inhibitor families, the most represented one among the DEGs detected at T1, with 11 out of 12 upregulated members, was undoubtedly A2M.…”
Section: In-depth Analysis Of Differential Gene Expression In the Mantlementioning
confidence: 66%
“…Several protease inhibitors belonging to five distinct families, i.e., kazal-type, kunitztype, tissue inhibitor of metalloprotease (TIMP), whey acidic protein (WAP), and alpha-2macroglobulins (A2M), were upregulated at T1. As previously noted by other authors [79], protease inhibitors are a recurrent theme in shell biomineralization proteomes, where they are believed to prevent the premature degradation of extracellular matrix proteins by the numerous proteolytic enzymes present in the extracellular space. Among these five protease inhibitor families, the most represented one among the DEGs detected at T1, with 11 out of 12 upregulated members, was undoubtedly A2M.…”
Section: In-depth Analysis Of Differential Gene Expression In the Mantlementioning
confidence: 66%
“…The encoded proteins are acidic because aspartic amino acids predominate (i.e., ASP-RICH). A putative role of acidic proteins has been suggested in clams where they are key components of the calcification process, possibly being involved in nucleation, inhibition, and orientation of crystal growth [ 18 ]. This is because Asp-/Glu or poly-Asp/poly-Glu-rich domains can bind high amounts of Ca 2+ [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A putative role of acidic proteins has been suggested in clams where they are key components of the calcification process, possibly being involved in nucleation, inhibition, and orientation of crystal growth [ 18 ]. This is because Asp-/Glu or poly-Asp/poly-Glu-rich domains can bind high amounts of Ca 2+ [ 18 ]. The finding that CcASP-RICH can bind calcium ions is partly supported by biochemical evidence previously obtained using the Stains-All dye [ 17 ], which showed that CcASP-RICH can exhibit calmodulin-like behavior and thus bind calcium ions.…”
Section: Discussionmentioning
confidence: 99%
“…Major proteins and the best matches of minor proteins were identified as SMPs of C. nippona in this study. Furthermore, SMPs of the other six molluscs including C. gigas [ 30 ], Atrina pectinata [ 15 ], Tridacna crocea [ 121 ], P. fucata [ 30 ], Lottia gigantea [ 122 ], and N. pompilius [ 49 ] were download and used for comparative analysis of shell proteomes. Functional domain annotations of SMPs were performed by searching against various databases, including SMART, CDD, Pfam, PROSITE patterns, PROSITE profiles, and SUPERFAMILY, using InterProScan (v 5.52–86.0) [ 101 ].…”
Section: Methodsmentioning
confidence: 99%